Harnessing ELT Innovations and Technology to Elevate English Language Teaching and Learning in Islamic School - Husain, Faisal Anwar; Almumtazah, Nadia Fakhrunnisa (Journal of English Education and Teacher Trainer, 2025)
This article aims to enhance teachers' use of innovation and technology in the learning and teaching process and to motivate students to be wise in their use of technology. At this time, technology continues to evolve; however, as teachers, we must keep up with the times in education. Learning that relies on textbooks and blackboards is starting to be left behind, as we need to adapt education to the technology that has developed today. This adaptation includes incorporating values of religion, such as respect, responsibility, and moderation so that children are not only skilled in using technology but also wise in its application. This article discusses the innovations and technologies used in teaching and learning English that are widely employed by teachers, as well as the challenges they face when implementing them in the classroom. Additionally, the article addresses how students can wisely utilize technology. In conclusion, the use of ELT Innovations and Technology can elevate ELT and the learning process.